Monitoring of data base management system for traffic light by using SCADA system / Mohd Khairul Anam Ujud - Ujud, Mohd Khairul Anam (2003)
In this paper traffic light monitoring system are improved, instead of using a conventional method which traffic light user also need to takes part in monitoring the traffic light, development of monitoring of data base management system for traffic light by using Supervisory and Data Acquisition (SCADA) system is being conducted. Traffic light event is being recorded in data logging system in which included in the SCADA system itself to show if the flow of the traffic follow as it should be or not. When fault is occur which is the connection of the wire is cutoff, message will be send to the operator and decision will be made by the operator if the traffic need to do a maintenance or the system only need to be reset. Fault in the system can be monitor and changers can be made from the Human Machine Interface (HMI) control panel.